ON EVOLUTIONARY STATUS OF STARS WITH THE R CrB PHENOMENON - Rosenbush, A. E. (Одеські астрономічні публікації, 2017)
Two key features are important for understanding the evolution of stars with the R Coronae Borealis variability: the state of high mass loss rate and the carbon overabundance. The hydrogen deficiency is a consequence of these two characteristics. This idea allows us to build one of several possible evolutionary chains from observable states of some stars: from a low mass star of the FG Sge type with a thin hydrogen shell through the phases of V854 Cen - R CrB - UV Gas to a star of the XX Cam type with hydrogen completely lost.